Dissociation Between Severity of Takotsubo Cardiomyopathy and Presentation With Shock or Hypotension. Issue 7 (12th April 2013) - Chong, Cher‐Rin; Neil, Christopher J.; Nguyen, Thanh H.; Stansborough, Jeanette; Law, Gin Way; Singh, Kuljit; Horowitz, John D.
Abstract Background Takotsubo cardiomyopathy (TTC) is increasingly well‐recognized as a cause of chest‐pain syndromes, especially in aging females. The most common complications of TTC occur in the first 24 hours post onset of symptoms and include shock and/or arrhythmias. Hypothesis We tested the hypothesis that the severity of early hypotension in TTC reflects the extent of myocardial involvement and dysfunction. Methods In 80 consecutive TTC patients, correlates of blood pressure on the day of admission were sought via univariate followed by multivariate analysis. Results Mean systolic blood pressure (SBP) on day 1 was 120 ± 24 (SD) mm Hg. During the first 3 days of admission, 39% of patients had SBP <90 mm Hg, and 9% died and/or required intra‐aortic balloon pump insertion. The extent of release of N‐terminal pro‐brain natriuretic peptide, with its potential correlate of associated vasodilator activity, varied inversely with pulmonary‐artery saturation, a measure of cardiac output. However, there was no significant relationship between normetanephrine release and SBP. On multivariate analyses there was no significant relationship between SBP and (1) wall‐motion score index (as an index of left‐ventricular systolic dysfunction) or (2) T2 enhancement on cardiac magnetic resonance imaging and peak N‐terminal pro‐brain natriuretic peptide (as indices of myocardial inflammation). Conclusions Although severe hypotension and shock occur commonly during acute stages of TTC, these complications are multifactorial in origin, probably representing a combination of impaired inotropic state and vasodilatation. Importantly, initial hypotension does not imply severe left ventricular inflammation or systolic dysfunction.